(untitled) (ENTHYMEMA, 2013)
The essay attempts to explain the modest popularity of Shakespeare in 18th and 19th century Italy, pointing out the role of a myth which posited the superiority of Italian language and culture in Europe which favoured the isolation of Italian theorizing on translation in comparison with other contexts.